Edukasi Gizi Seimbang dan Pencegahan Konsumsi Minuman Manis pada Siswa Sekolah Dasar - Apri Yulda; Titis Wulandari; Sella Puspita Sari; Indah Ayu Lestari; Poppy Demitri; Indi Lulu Almaknun; Lailahnajmah; Farhan Firmansya; Farhan Naofal Amjad (LPPM UNIVERSITAS MUHAMMADIYAH MUARA BUNGO, 2026)
Elementary school-aged children are a vulnerable group to nutritional problems due to unhealthy consumption patterns, particularly high consumption of junk food and sugary drinks. Lack of understanding of balanced nutrition can impact students' health, concentration in learning, and academic achievement. This community service activity aims to increase students' knowledge about the importance of nutritious food and the dangers of consuming sugary drinks. The activity was carried out at SD Negeri 101 Muara Bungo with a target of 61 third-grade students. The methods used included a pretest, interactive counseling, discussion, and posttest. The results of the activity showed an increase in the average score from 95.00% in the pretest to 97.05% in the posttest. These results indicate that health education is effective in increasing students' understanding and has the potential to form healthy lifestyle behaviors from an early age.